2009
DOI: 10.1208/s12249-009-9188-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Budesonide Compression-Coated Tablets for Colonic Delivery

Abstract: The purpose of this study was to formulate budesonide (BUD) compression-coated tablets for colonic specific delivery. Pectin and guar gum were used as enzyme-dependent polymers. For comparison purposes, both pH- and time-dependent polymers were also tried. In vitro release studies were carried out at different pH (1.2, 6.8, and 7.4). Therapeutic efficacy of the prepared tablets compared to commercially available capsules and enema were evaluated in trinitrobenzenesulfonic acid-induced rabbit colitis model. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Although several polysaccharides such as guar gum, pectin, sodium alginate, locust bean gum, chitosan, boswellia gum, and xanthan gum have been used as compressioncoating material (16)(17)(18)(19)(20), carboxymethyl xanthan gum (CMXG), neither alone nor in combination with other polysaccharides, has been explored to assess its suitability for the development of compression-coated colon-targeted tablets. In a previous study, we evaluated Ca +2 ion cross-linked CMXG (Ca-CMXG) matrix tablets for colon delivery of prednisolone (PDL) (21).…”
Section: Introductionmentioning
confidence: 99%
“…Although several polysaccharides such as guar gum, pectin, sodium alginate, locust bean gum, chitosan, boswellia gum, and xanthan gum have been used as compressioncoating material (16)(17)(18)(19)(20), carboxymethyl xanthan gum (CMXG), neither alone nor in combination with other polysaccharides, has been explored to assess its suitability for the development of compression-coated colon-targeted tablets. In a previous study, we evaluated Ca +2 ion cross-linked CMXG (Ca-CMXG) matrix tablets for colon delivery of prednisolone (PDL) (21).…”
Section: Introductionmentioning
confidence: 99%
“…Polymethacrylates are widely used in pharmaceutical delivery systems for sustained drug delivery, 10) hot melt extrusion, 11,12) microencapsulation, 13) nanoparticle, 14,15) antiretroviral drug delivery, 15,16) floating microspheres, 17) colon delivery 18,19) and transdermal drug delivery. 20) In our previous studies we showed the effect of thermal treating on the release of indomethacin 8) and diclofenac sodium 9) from acrylic matrix tablets and mechanistically studied the effect of heat-treating on physicochemical structure of tablet.…”
mentioning
confidence: 99%
“…These results may be explained on the basis that the release retardation imparted by tablets coated with 10% HPMC provided minimal gastric and intestinal absorption but allowed high drug release in the colon. The successful use of compression coated tablets of budesonide in treatment of ulcerative colitis has been documented [30]. …”
Section: Histopathological Evaluation Of Rabbit Colonmentioning
confidence: 99%